1999
DOI: 10.3758/bf03211950
|View full text |Cite
|
Sign up to set email alerts
|

Effect of masker level on infants’ detection of tones in noise

Abstract: In adult listeners, the signal-to-noise ratio at masked threshold remains constant with increases in masker level over a wide range of stimulus conditions. This relationship was examined in 7-month-old infants by obtaining masked thresholds for .5- and 4-kHz tones presented in four levels of continuous masking noise. Adults were also tested for comparison. Masker spectrum levels ranged from 5 to 35 dB/Hz for .5-kHz tones, and from -5 to 25 dB/Hz for 4-kHz stimuli. Thresholds were determined for stimuli of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…However, for infant listeners, the difference between DLs for 10-and 100-msec increments tended to be large at low levels of the standard and to decrease with increasing intensity at both low and high frequencies. This pattern is very similar to results obtained for infants' temporal integration of low-frequency tones in increasing levels of masking noise (Berg & Boswell, 1997). Thus, despite the different characteristics of temporal integration in detection and level discrimination paradigms, developmental trends appear to be the same for the two tasks.…”
Section: Level Of Standard (Db Susupporting
confidence: 74%
“…However, for infant listeners, the difference between DLs for 10-and 100-msec increments tended to be large at low levels of the standard and to decrease with increasing intensity at both low and high frequencies. This pattern is very similar to results obtained for infants' temporal integration of low-frequency tones in increasing levels of masking noise (Berg & Boswell, 1997). Thus, despite the different characteristics of temporal integration in detection and level discrimination paradigms, developmental trends appear to be the same for the two tasks.…”
Section: Level Of Standard (Db Susupporting
confidence: 74%
“…Although the differences in EMLs between infants and adults found in the present study are similar to those observed for air-conducted masked behavioral studies, the signal-tonoise ratios (SNRs) for infants compared with adults differ slightly from the findings of a visual reinforcement study conducted by Berg and Boswell (1999). In their study, SNRs for four different masking levels were determined at 500 and 4000 Hz by finding the masked thresholds for each individual masker.…”
Section: Effective Masking Levelssupporting
confidence: 63%
“…Temporal integration results from 3 to 7 month old infants ͑Berg, 1991; Werner and Marean, 1991;Berg and Boswell, 1999͒ have generally been consistent with greater temporal integration than found for adults due to relatively poor infant thresholds for short-duration signals consisting of either clicks or 10-16 ms tone bursts. Interestingly, the report by Berg and Boswell ͑1999͒ indicated that infants' temporal integration was more adult-like at higher masker levels, and that the adult/infant difference in temporal integration was absent for a relatively highfrequency ͑4-kHz͒ signal.…”
Section: Introductionmentioning
confidence: 69%